2015
DOI: 10.1080/14783363.2015.1068688
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for implementing TQM through the EFQM model in Spain: an empirical investigation

Abstract: This paper presents the results of the empirical study conducted in 68 Spanish firms which are following the implementation process of the Total Quality Management (TQM) through the EFQM excellence model, according to the Excellence in Management Club (the official representative and partner of EFQM in Spain which is a non-profit making organisation with the aim of being the reference and meeting point for organisations on their way towards excellence). The objective of this paper is to analyse the motivations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 59 publications
(123 reference statements)
2
19
0
4
Order By: Relevance
“…The Model includes nine criteria and scientists and managers have established three linkage axes in the model, where the 'Personnel Axis' links the criteria Leadership, People, Processes, People Results and Business Results (Nabitz, Jansen, Van der Voet, & Van den Brink, 2009). In this sense, most of the studies have focused their attention on evaluating the impact of the EFQM model on business results (Gómez-López, Serrano-Bedia, & López-Fernández, 2016), although some, such as the one of Samuelsson and Nilsson (2002) centred its attention on the fact that self-assessment approaches contribute to the improvement of the organization and encourage employee involvement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Model includes nine criteria and scientists and managers have established three linkage axes in the model, where the 'Personnel Axis' links the criteria Leadership, People, Processes, People Results and Business Results (Nabitz, Jansen, Van der Voet, & Van den Brink, 2009). In this sense, most of the studies have focused their attention on evaluating the impact of the EFQM model on business results (Gómez-López, Serrano-Bedia, & López-Fernández, 2016), although some, such as the one of Samuelsson and Nilsson (2002) centred its attention on the fact that self-assessment approaches contribute to the improvement of the organization and encourage employee involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, literature on quality management (QM) has shown the positive effects that the adoption of QM systems and models have for performance management (Bayo-Moriones, Merino-Díaz-de-Cerio, Escamilla- de-León, & Selvam, 2011). However, Gómez-López et al (2016) state that EFQM's enablers do not always have a significant effect on results. Moreover, Doeleman, Ten Have, and Ahaus (2013) cautioned that best practices do not necessarily guarantee performance improvements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These can be categorized as both internal and external reasons. On the other hand, according to Gómez-López, Serrano-Bedia, and López-Fernández, the motivations can be grouped into: external market reasons, external reasons of requirements and internal institutional reasons (Gómez-López, Serrano-Bedia, & López-Fernández, 2015). Heras-Saizarbitoria, Casadesus, and Marimon (2011) found that the critical drivers for implementing the EFQM model were of an internal character which included: productivity issues, optimization of resources, improvement of the quality of products and services, and reduction of costs.…”
Section: Benefits Of Bemsmentioning
confidence: 99%
“…Studies analysing relationships between BEM factors are limited, focusing mainly on models and tools such as Benchmarking, Balanced Scorecard, International Standards Series (ISO9000), and Six-Sigma (Dahlgaard-Park et al, 2013). Studies on BEMs have focused on descriptive comparisons between models (e.g., Lee & Lee, 2013); effects from the use of BEMs (Bayo-Moriones et al, 2011;Stok et al, 2009); organisations winning excellence awards (Boulter et al, 2013;Escrig & de Menezes, 2015); constraints and challenges of applying BEMs (Gómez-López et al, 2016;Heras-Saizarbitoria et al, 2011); differences in stakeholder perceptions of business excellence adoption (Camison, 1996); and its integration with other tools (Peng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%